The Burden of Urinary Tract Infections: Identifying Knowledge Gaps and Preventive Strategies among Female Undergraduates in the University of Benin - Egbochuku, Obiageli Ogochukwu; Atedhor, Chinwe Nneamaka (NIU Journal of Educational Research, 2025)
Urinary Tract Infections (UTIs) are becoming a global burden, with the leading causal organism being Escherichia Coli (E.coli). It is increasingly becoming an issue of concern among undergraduates due to lifestyle and other environmental factors. This study aimed to identify knowledge gaps and preventive strategies for UTIs among female undergraduates of University of Benin. Descriptive survey was conducted among female undergraduates of the university. Multistage sampling was used to select 234 respondents for the study. A pre-tested multiple-choice question was used to elicit information on the knowledge and preventive practices of the respondents. Data was analyzed using descriptive statistics of frequency counts and percentages while inferential statistics using t-test and Pearson correlation was used to show difference and relationship between the variables of interest. Findings indicate that about 46% of the respondents had moderate level of knowledge while responses varied for preventive practices with only 17.5% wiping the genital area correctly from front to back. 42.3% of the respondents change their sanitary towel after over 12 hours, 28.2% urinate less than four times daily while only 35.5% wash their genitourinary after using the rest room. The study emphasizes the need to intensify efforts to improve knowledge on UTIs among students as it is expected to impact their preventive practices. While UTIs can be treated, they can lead to more serious infections and even kidney damage if left untreated, so mass enlightenment is imperative, especially among this susceptible population. Keywords: Urinary Tract Infections, Female undergraduates, Knowledge, Preventive practices, Nigeria.